Pemberdayaan Masyarakat Desa Sidomulyo melalui Edukasi dan Sosialisasi Pemanfaatan Limbah Kulit Kopi menjadi Teh Cascara - Mirriyadhil Jannah; Ahmad David Royyifi Arifin; Eko Priyantono; Intan Ria Neliana; Lita Meilina; Brihatsama; Nur Latifatul Qodriyah (Jurnal Pengabdian Masyarakat IPTEKS, 2026)
Coffee husk (cascara) is an agricultural waste that has not been optimally utilized by the community, despite its potential as a functional herbal beverage with economic value. This community engagement program aimed to enhance public knowledge regarding the benefits and potential of cascara through an educational approach. The activity was conducted in Sidomulyo Village, Silo Sub-district, Jember Regency, involving 20 participants from various community groups. The program was carried out in five stages: problem identification, pre-test, initial socialization, educational material delivery, and post-test. The results showed a significant increase in participants’ understanding, with the number of correct answers rising from an average of 5 to 16 respondents per question. This indicates that locally-based education is effective in raising awareness about coffee waste management. Such educational interventions can serve as an initial step toward community empowerment and the development of cascara-based microenterprises.